PERAN BIDAN TERHADAP KEPATUHAN IBU HAMIL DALAM MELAKUKAN KUNJUNGAN ANTENATAL CARE PADA MODEL CONTINUITY OF CARE - Azizah, Atika Nur (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Antenatal services are health services performed by health workers, especially midwives during their pregnancy according to antenatal care standards. Compliance of pregnant women in antenatal care is very important to improve mental and physical health during pregnancy. This study aims to determine the role of midwives on the compliance of pregnant women in conducting antenatal care visits in the Continuity of Care model. The study design was cross-sectional with a sample of 100 pregnant women who had attended the Continuity of Care model. Based on multivariable analysis, midwives who do not support have a role to make pregnant women disobedient in conducting antenatal care examinations 3 times compared to supporting midwives.Keywords: Antenatal Care, Compliance of Pregnant Women, The Role of Midwives